2021
DOI: 10.1039/d0ew00766h
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of clogging in porous media induced by microorganisms using a microfluidic application

Abstract: The presence of microorganisms could alter the porous medium permeability, which is vital for several applications, including aquifer storage and recovery (ASR), enhanced oil recovery (EOR) and underground hydrogen storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Biofilm formed by T. distorta was very heterogeneous. Roughness was calculated according to Tang et al [32] by the use of Equations ( 1) and ( 2) and is shown in Figure 2c. The roughness exceeded 50% of biofilm thickness during the first 10 days and stabilized to 40% after.…”
Section: Biofilm Monitoring Using Octmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formed by T. distorta was very heterogeneous. Roughness was calculated according to Tang et al [32] by the use of Equations ( 1) and ( 2) and is shown in Figure 2c. The roughness exceeded 50% of biofilm thickness during the first 10 days and stabilized to 40% after.…”
Section: Biofilm Monitoring Using Octmentioning
confidence: 99%
“…The µCT technique is not only a useful tool to visualize bacterial communities, it also allows the possibility of insight into the structures of bacterial biofilms and the relationship between biofilm structure and its functions, for example, biogenic calcite minerals as diffusion barriers [31]. Often µCT scans are used to obtain a 3D model for a simulation (e.g., CFD) or for 3D printing [32]. Due to poor contrast differences in µCT analysis between biofilm and biocarrier [33], often a contrast agent is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-particle image velocimetry (μ-PIV) is an accurate and well-established optical technique for quantifying microscopic flows with good spatial resolution. 15,16 It has applications in EOR, 8 CO 2 sequestration, 17−19 and clogging detection 20 in the porous medium. This technique has been used to obtain the pore-scale velocity vector map of immiscible two-phase flow in a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experiments and simulations have also been performed to investigate the pore-scale flow physics during two-phase flow in the porous medium. Methods such as microcomputed tomography, micro-particle tracking velocimetry (micro-PTV), particle image velocimetry (PIV), and micro-particle image velocimetry (micro-PIV) have been used to visualize and quantify the flow in 2D porous micromodels. The micro-particle image velocimetry (μ-PIV) is an accurate and well-established optical technique for quantifying microscopic flows with good spatial resolution. , It has applications in EOR, CO 2 sequestration, and clogging detection in the porous medium. This technique has been used to obtain the pore-scale velocity vector map of immiscible two-phase flow in a porous medium. ,, In the μ-PIV technique, two successive images of tracer particles in the flowing fluid are captured at a time delay (Δ t ) using a high-speed camera.…”
Section: Introductionmentioning
confidence: 99%
“…In microfluidic systems, the microscale filter used for microparticle sorting and filtration is a feasible and deeply developed technology that has been also widely adopted in macroscale industries. , Different types of microscale filter units, including pillar-type, weir-type, and porous membrane filters, have been studied and explored. These methods can sort, filtrate, and trap cells according to their size or shape and are normally able to be integrated within microsystems. However, these applications also face problems of clogging and unexpected trapping, potentially inducing a low working efficiency after long-term running and requiring frequent maintenance.…”
mentioning
confidence: 99%